(untitled) (American Journal of Islam and Society, 2003)
This book arose from a series of conferences held as part of the Toda lnstitute’s research project, Human Security and Global Governance, initiated in 1996. The book’s ambitious title matches its expansive structure. Aside from 16 chapters divided equally into Parts One and Two, there is a preface by Hans Kung, an introduction by the editors, and a lead chapter by Tehranian. Tn addition, the appendix cites a 15-item declaration by the peace scholars attending the Okinawa conference in 2000 to promote mutual respect and understanding among alt religious and secular traditions of civility. Tehranian and Chappell’s "Introduction" situates the need for dialogue among civilizations in light of 9/11, which, they argue, presents both challenges to human security and a critical opportunity for the emergence of a new, just world order. The editors read 9/11 not as a lone act of insanity, but as an act that represents global resentment against how the world is run. They argue that unlike poverty in traditional systems that provide a social safety net, modern poverty in the "global fishbowl" is experienced as more humiliating and infuriating, because communication technologies make possible increased awareness of relative deprivation. In chapter I, "lnformatic Civilization: Promises, Perils, Prospects," Tehranian extends the introduction’s claims that in the wake of the New World Disorder, we now have the opportunity to forge a global civilization fostered by dialogue, which itself is made possible by new technologies. This section raises my hackles, for Tehranian’s use of"civilization" vacillates between the singular and the plural. That is, should we think of "civilization" as a uniform, linear progression of human society based, as Tehranian argues, upon a mode of production, or should we think of"civilizations" in terms of different cosmologies derived, for instance, from the world religions? ...